Efektivitas pembangkit listrik tenaga mikrohidro sebagai penyedia energi baru terbarukan berbasis komunitas: (Studi Kasus: PLTMH Anggi, Kabupaten Pegunungan Arfak dan PLTMH Kali Ombak, Kabupaten Maybrat, Papua Barat) - Ofi Shofiyah; Calista Mutia Gunandar; Vincensia Tasha Devi Ariyanti (Social, Ecology, Economy for Sustainable Development Goals Journal, 2023)
Indonesia is currently trying to achieve the number 7 sustainable development target in the energy sector through renewable energy. This is evidenced by achieving an electrification ratio of 99.20% in Indonesia, with one of Indonesia's renewable energy potentials in micro hydro to provide electricity in rural areas. This research will discuss the potential for providing micro-hydro power plants (PLTMH) outside Java, especially in West Papua Province. The research was conducted qualitatively, using a comparative study research method to compare research variables, namely the operational efficiency of the Anggi PLTMH in Anggi District, Arfak Mountains, West Papua, and the Kali Ombak PLTMH in South Mare District, Maybrat Regency, West Papua from an environmental aspect (analysis of electricity production from the PLTMH, carbon dioxide emissions resulting from the operation of the PLTMH, and a comparison of environmental impacts based on the type of environmental documents) and social aspects (reduction in the cost of community electricity due to the implementation of the PLTMH, the number of households channeled electricity, and the implementation of community involvement in the management of the PLTMH). The study results show that the Anggi PLTMH is more effective than the Kali Ombak PLTMH in providing micro-hydropower in terms of electricity production capacity, reduction of carbon dioxide emissions, and reduction of electricity costs. PLTMH Anggi can generate electricity of 108.9 kW, reduce carbon dioxide by 2.1693 tons of CO2, and save electricity costs of Rp 4,441,891.608, which is superior to PLTMH Kali Ombak. However, currently, there is still a need for development in the social field in the operation of PLTMH, both PLTMH Anggi and PLTMH Kali Ombak, in the form of community involvement because active community involvement has not yet been realized, both in the planning and maintenance stages of PLTMH and the socialization of environmental impacts based on the type of environmental documents to be able to manage the impact perspective. The community's negative attitude toward PLTMH activities.